Innovative strategies for treatment of soft tissue injuries in human and animal athletes - Hoffmann, A.; Gross, G. (Genetics and Sports, 2009)
Our aim is to review the recent progress in the management of musculoskeletal disorders. We will cover novel therapeutic approaches based on growth factors, gene therapy and cells, including stem cells, which may be combined with each other as appropriate. We focus mainly on the treatment of soft tissue injuries - muscle, cartilage, and tendon/ligament for both human and animal athletes. The need for innovative strategies results from the fact that despite all efforts, the current strategies for cartilage and tendon/ligament still result in the formation of functionally and biomechanically inferior tissues after injury (a phenomenon called `repair` as opposed to proper `regeneration`), whereas the outcome for muscle is more favorable. Innovative approaches are urgently needed not only to enhance the outcome of conservative or surgical procedures but also to speed up the healing process from the very long disabling periods, which is of special relevance for athletes. (Autorreferat)